Protecting the commons : - Burger, Joanna (Island Press, 2001)
Contributors from the biological, political, and environmental sciences offer ideas on the conservation management of lands, waters, and resources that are not legally owned and controlled by a single private entity, such as the ocean and coastal areas, the atmosphere, public lands, freshwater aquifers, and migratory species. Their 14 studies cover local, regional, cross-boundary, and global commons and decision-making tools.